PRODUKTIVITAS KERJA SETELAH ADANYA PENGURANGAN KARYAWAN KETIKA KENAIKAN UPAH MINIMUM DI PT. SINAR PRATAMA CEMERLANG - Chrestony Soeyono Pusung; Maria Heny Pratiknjo; Evelin J.R. Kawung (AGRI-SOSIOEKONOMI, 2021)
This study aims to figure out about work productivity after the reduction of employees at PT. Sinar Pratama Cemerlang. This research used descriptive and qualitative approach that aims to overview a phenomenon that occurs in this case the phenomenon of the impact of an increase in the city minimum wage on workers productivity in Manado City. Data collection techniques used in this research are observation, interview, and documentation methods. The results of this study shows that work productivity after a reduction in employees when there is an increase in the minimum wage at PT. Sinar Pratama Cemerlang as a whole is classified as good in terms of quantity of work, quality of work, and punctuality.